1991
DOI: 10.1128/aem.57.10.2956-2962.1991
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of plasmid- and chromosome-mediated iron uptake systems in Vibrio anguillarum strains of different origins

Abstract: We investigated the incidence of plasmid-mediated and chromosome-mediated iron uptake systems in strains of Vibrio anguillarum that belong to serotypes 01 and 02 and were isolated from different fish species and in different geographic areas. All of the strains gave positive reactions in CAS agar medium and in the Arnow test, which indicated that catechol types of siderophores were produced. The majority of V. anguillarum serotype 01 strains harbored a 65-kb plasmid similar to plasmid pJMl from strain 775, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…A second iron-uptake system is present in V. anguillarum which functions independently of the pJM1 ironsequestering system and its respective OM2 receptor protein, based on chromosomally encoded mediation (Lemos et al 1988). The pJM1 plasmid series is present in most V. anguillarum O1 strains but is absent in serotype O2 while the chromosome-mediated iron-uptake system exists in both the O1 and O2 serotype (Conchas et al 1991). Vibrio anguillarum biotypes which exhibit chromosomemediated iron uptake do so using the siderophore vanchrobactin as opposed to anguibactin which is used in plasmidmediated iron uptake (Mackie & Birkbeck 1992;Soengas et al 2006).…”
Section: Iron Appropriation and Haemolysismentioning
confidence: 99%
“…A second iron-uptake system is present in V. anguillarum which functions independently of the pJM1 ironsequestering system and its respective OM2 receptor protein, based on chromosomally encoded mediation (Lemos et al 1988). The pJM1 plasmid series is present in most V. anguillarum O1 strains but is absent in serotype O2 while the chromosome-mediated iron-uptake system exists in both the O1 and O2 serotype (Conchas et al 1991). Vibrio anguillarum biotypes which exhibit chromosomemediated iron uptake do so using the siderophore vanchrobactin as opposed to anguibactin which is used in plasmidmediated iron uptake (Mackie & Birkbeck 1992;Soengas et al 2006).…”
Section: Iron Appropriation and Haemolysismentioning
confidence: 99%
“…, 2009). It is unclear which is the possible role, if any, of these genes in the chromosome, although it seems clear that they are not expressed, at least in serotype O2 strains, since they are disrupted by IS elements and FatA protein was never detected in serotype O2 strains (Conchas et al. , 1991; Balado et al.…”
Section: Common Features Between Anguibactin‐ and Vanchrobactin‐mediamentioning
confidence: 99%
“…Interestingly, there are some highly virulent serotype O1 strains that do not harbour pJM1‐like plasmids. Iron uptake in these strains is actually mediated by vanchrobactin (Conchas et al. , 1991; Naka et al.…”
Section: Evolutionary Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to anguibactin, V. anguillarum 775 (pJM1) can transport exogenous siderophores such as vanchrobactin and enterobactin (Naka et al, 2008;Balado et al, 2009;. One of them, vanchrobactin, is a chromosomally encoded siderophore produced by natural pJM1-less V. anguillarum O1 strains and other serotype strains (Lemos et al, 1988;Conchas et al, 1991;Balado et al, 2006Balado et al, , 2008Soengas et al, 2006). We previously showed that outer membrane proteins, FvtA and FetA, are involved in the transport of these exogenous siderophores in V. anguillarum 775(pJM1) .…”
Section: Introductionmentioning
confidence: 99%